Exploring the bone sparing effects of postbiotics in the post-menopausal rat model - Nima Montazeri-Najafabady; Younes Ghasemi; Mohammad Hossein Dabbaghmanesh; Yousef Ashoori; Pedram Talezadeh; Farhad Koohpeyma; Seyedeh Narjes Abootalebi; Ahmad Gholami (BMC, 2021)
Abstract Background Post-menopausal osteoporosis is a concern of health organizations, and current treatments do not seem enough. Postbiotics as bioactive compounds produced by probiotics may be an attractive alternative for bone health. In this study, we prepared, formulated, and compared the effects of cell lysate and supernatant of five native probiotic strains (Lactobacillus acidophilus, Lactobacillus reuteri, Lactobacillus casei, Bifidobacterium longum, and Bacillus coagulans) in ovariectomized (OVX) rats. Methods The probiotic strains were isolated, and their cell-free supernatants and biomasses as postbiotics were extracted and formulated using standard microbial processes. The Sprague-Dawley rats were fed by 1 × 109 CFU/ml/day postbiotic preparations for 4 weeks immediately after ovariectomy. Dual-energy X-ray absorptiometry (DEXA) scans were accomplished to evaluate femur, spine, and tibia BMD. The serum biochemical markers [calcium, phosphorus, and alkaline phosphatase] were assessed. Results Postbiotics could considerably improve the global and femur area in OVX rats. In the case of global bone mineral density (BMD), Lactobacillus casei lysate and supernatant, Bacillus coagulans lysate and supernatant, lysate of Bifidobacterium longum and Lactobacillus acidophilus, and Lactobacillus reuteri supernatant significantly increased BMD. We found Bacillus coagulans supernatant meaningfully enriched tibia BMD. Conclusion Postbiotic could ameliorate bone loss resulting from estrogen deficiency. Also, the effects of postbiotics on different bone sites are strain-dependent. More clinical studies need to explore the optimal administrative dose and duration of the specific postbiotics in protecting bone loss.